Maximum economic yield of the western rock lobster fishery of Western Australia after moving from effort to quota control. (January 2015) - Caputi, Nick; de Lestang, Simon; Reid, Chris; Hesp, Alex; How, Jason
Abstract: The western rock lobster ( Panulirus cygnus ) fishery is Australia's most valuable single-species fishery, worth AUD$200–$400 million annually. Stock assessment for this fishery utilises the puerulus settlement to predict recruitment to the fishery 3–4 years later. This predictive ability has been particularly useful recently, due to an unprecedented period of low settlement between 2006/07 and 2012/13. Pre-emptive management action (~70% effort reduction) was taken to provide greater protection to the breeding stock which also moved the fishery to the maximum economic yield (MEY) level of effort for the projected recruitment. In 2010/11, the fishery moved from an effort-controlled to a quota-controlled fishery, which led to changes in fishing practices resulting in reductions in fishing costs and increases in lobster prices of about US$16/kg. This provided a unique opportunity to compare an MEY assessment under effort and quota controls. The MEY assessment under quota controls for a 5-year period indicated that annual harvest rates of 37–47% of legal biomass will achieve catches of 5780–7370 t. in 2014. This MEY target harvest range, which complements existing sustainability reference points based on egg production, is robust to a range of costs, prices and profit discount rates. This catch range enables industry/managers to take into account marketing implications and social issues (e.g. employment) in quota setting and therefore could be considered a socio-economic target. The MEY level of fishing has increased egg production to well above threshold levels that were based on maximum sustainable yield, providing the fishery with increased resilience when faced with environmental perturbations. This enables consideration for relaxing some existing biological controls, e.g. setose (mature) females, females above a maximum size, and lobsters 76–77 mm carapace length. The relaxation of these controls is estimated to increase profits by about AUD$15 million annually due to higher catch rates and reduced fishing effort while maintaining egg production well above threshold levels. Graphical abstract: Highlights: Western rock lobster fishery moved to MEY initially as an effort-controlled fishery. Fishery changed to an ITQ fishery which further improved economic performance. MEY target adopted complementing sustainability reference points for egg production. Stock assessment uses puerulus settlement to predict recruitment 3–4 years later. MEY fishing has increased egg production providing increased resilience to fishery.